Risk awareness and sexual relationships among youth in the Johannesburg area - F G Netswera (AOSIS, 2002)
The increase in the reported rate of the human immunodeficiency virus (HIV), acquired immune deficiency syndrome (AIDS) and sexually transmitted infections among the youth of South Africa has led to a rise in awareness campaigns to combat these epidemics. Opsomming Die toename in die aangemelde koers van menslike immuniteits-gebreksindroom (MIV), verworwe immuniteitsgebreksindroom (VIGS) en seksueel oordraagbare infeksies onder die jeug in Suid-Afrika het tot 'n toename in bewuswordingsveldtogte gelei om hierdie epidemie hok te slaan. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.